Woody species diversity and regeneration patterns in Osun-Osogbo sacred grove, Nigeria (2017)
Osun-Osogbo Sacred Grove in Nigeria is one of the major biodiversity hotspots in sub-Saharan Africa with high plant diversity that has suffered considerable human-induced disturbance in the recent times. Therefore, this study aimed to quantify the canopy species diversity and regeneration pattern in the Sacred Grove. Three (0.09ha) plots were sampled in each identified forest type (old-growth, secondary-regrowth, and riparian forests) for the inventory of tree / sapling stems, and nested quadrats (5 x 5m2) for seedlings. All stems enumerated were identified to species level. Data on diameter-at-breast height (dbh) and number of individuals per species were collected by plot. The patterns of tree (dbh ≥ 10 cm) distribution and regenerating (dbh ≤ 10 cm) population were examined using Detrended Correspondence Analysis (DCA) while the regeneration status of the grove was assessed by comparing the Importance Value Indices (IVI) of the current stocking and regenerating populations of the tree species. A total of 75 vascular species representing 66 genera and 30 families were identified. Fabaceae (13 spp), Apocynaceae (8 spp.), Euphorbaceae (7 spp.) and Rubiaceae (7 spp.) contributed 47.5% of the flora. The first two component axes of DCA (79.59%) delineated three community assemblages along disturbance gradient in the tree population. In addition, the first two component axes of DCA (107.70%) identified four communities along composition and disturbance gradients in the regenerating population. Analysis of IVI indicated that Dialium guineense (4.11), Funtumia elastic (6.08) and Cola millenii (5.06) were dominant and the most widely distributed tree species in the Grove. Osun Sacred Grove is rich in vascular species diversity with diameter distribution showing poor growth and inadequate self- replacement of emergent tree species. Gap creation and appropriate cultural practices should be undertaken to improve the regeneration of the emergent species.